2013
DOI: 10.1039/c2cp44436d
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of small micropores in high CO2 uptake

Abstract: Microporous carbon materials with extremely small pore size are prepared by employing polyaniline as a carbon precursor and KOH as an activating agent. CO(2) sorption performance of the materials is systematically investigated at the temperatures of 0, 25 and 75 °C. The prepared carbons show very high CO(2) uptake of up to 1.86 and 1.39 mmol g(-1) under 1 bar, 75 °C and 0.15 bar, 25 °C, respectively. These values are amongst the highest CO(2) capture amounts of the known carbon materials. The relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
187
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 52 publications
29
187
3
Order By: Relevance
“…Improved CO2 retention capacities have been ascribed to even smaller diameters as well (Martín et al, 2010;Wahby et al, 2010;Wei et al, 2012;Sethia and Sayari, 2015). Zhang et al (2013) described that critical pore size increased with decreasing adsorption temperature and found that micropores with sizes below 0.54, 0.7, and 0.8 nm were determinant for adsorption at 75, 25, and 0°C, respectively . However, inconsistencies between authors are common depending on the conditions or characteristics studied, and seeking an advanced adsorbent is still very much empirical (Martín et al, 2010).…”
Section: Adsorption Equilibrium Studiesmentioning
confidence: 99%
“…Improved CO2 retention capacities have been ascribed to even smaller diameters as well (Martín et al, 2010;Wahby et al, 2010;Wei et al, 2012;Sethia and Sayari, 2015). Zhang et al (2013) described that critical pore size increased with decreasing adsorption temperature and found that micropores with sizes below 0.54, 0.7, and 0.8 nm were determinant for adsorption at 75, 25, and 0°C, respectively . However, inconsistencies between authors are common depending on the conditions or characteristics studied, and seeking an advanced adsorbent is still very much empirical (Martín et al, 2010).…”
Section: Adsorption Equilibrium Studiesmentioning
confidence: 99%
“…This is surprising because most previous studies have noted a widening of the adsorption knee at higher activation temperature. 29,56,57,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] The level of porosity generated, as judged by the amount of nitrogen adsorbed, increases modestly for samples prepared at higher activation temperature despite the non-changing nature and shape of the isotherms. The isotherms of the compactivated carbons are similar to those of analogous conventionally activated carbons except that they exhibit higher amounts of nitrogen sorption.…”
Section: Yield and Properties Of Activated Cnl1 Carbonsmentioning
confidence: 99%
“…The hydrogen-based fuel cells 2,3 , an immediate and effective CO 2 mitigation can be pursued by the 41 adoption of appropriate post combustion technologies. The use of porous solids for CO 2 capture 4 towards ultramicropores 13,26,[29][30][31] .…”
mentioning
confidence: 99%